COMMUNITY SERVICE THROUGH RELIGIOUS EDUCATION FOR MIGRANT CHILDREN IN MALAYSIA DURING RAMADAN - Dwita Nurulita; Yasin Nurfalah (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2025)
This Community Service may be a little different from the usual PKM activities because of the location point in the neighboring country, aiming to strengthen the learning system with a community-based approach and Learning Activities as well as strengthening religious education during Ramadan through interactive learning activities, Islamic studies, worship guidance, and Islamic character development.The sustainability of this program can be maintained by increasing cooperation between the community, educational institutions, and local government. However, there is still a lack of transparency regarding the learning program due to limited permits by some parties in Malaysia. Of course, the hope of every studio manager about the continuity of the learning process calmly and without obstacles is the desire of every manager. The evaluation results show an increase in Islamic understanding, Qur'an reading skills, increased student comprehension and active community participation in supporting their children's education.